The influence of religiosity, parental and peer attachment on hedonistic behavior among Malaysian youth - Hamzah, Siti Raba'ah; Suandi, Turiman; Hamzah, Azimi; Tamam, Ezhar (Elsevier, 2014)
Drawing from ecological system theory, the current study addresses the connection between environment and youth development and what they actually engage in. This study examined contributors of hedonistic behavior among youth in Malaysia. A sample of 103 undergraduate students from diverse backgrounds participated in the study. Using a quantitative survey methodology, self-administered questionnaires measuring parental and peer attachment, religiosity personality and worldview were used to identify predictors of hedonistic behavior among youth. The finding showed both, parental and peer attachment behavior moderated the relationships between religiosity and present-hedonistic values and behavior.